FAKTOR - FAKTOR YANG MEMPENGARUHI PEMBELIAN PRODUK BUAH NIPAH (USAHA MILIK BU FITRIANI DI KOTA LANGSA) - Felix Hisarma Lumban Gaol; Cut Gustiana; Supristiwendi Supristiwendi (Bajang Institute, 2023)
Difficulty developing is a problem that often occurs for business owners due to a lack of understanding of the factors that cause consumer behavior in their decision to buy a product. This research aims to analyze the factors that influence the decision to purchase processed nipah fruit products at Bu Fitriani's nipah fruit soup business in Gampong Timbang Langsa, Langsa Baro District, Langsa City. The research uses a causal design. The data collection method uses primary data and secondary data which are qualitative and quantitative in nature with the questionnaire measurement scale being the Likert scale. The population is all consumers and the sample was selected as 60 respondents using the incidental sampling method. The data analysis method uses multiple linear regression which is processed using IBM SPSS Statistics 22. The research results show that there is a positive and significant influence of Location, Price Perception, Lifestyle and Service on Purchasing Decisions. Meanwhile, product diversity has a negative and insignificant effect on purchasing decisions, which will later become evaluation material to be improved so that the business can develop further in the future